Quantum Learning of Eel Dr. C: Maximizing Students’ Civics Education Achievement - ., Iswan; Hassan, Zainudin (International Journal of Engineering and Technology, 2018)
The aims of this research are: (1) to investigate the effectiveness of Quantum  Learning  of EEL Dr. C in maximizing students’ civics education achievement, (2) to find out to what extent Quantum Learning of EEL Dr. C influences students’ civics education achievement. This is a quantitative research study which applied quasi-experimental research design. A total number of 60 students of State Primary School 1 Cirendeu,  Ciputat, South Tangerang, Indonesia participated in this study.These subjects were directly assigned into experimental and control classes. A set of multiple choice pre- and post-test was used to collect the data after being validated. The independent t-test was used in analyzing the data. The findings of the research revealed that there is a significant difference of mean scores of students’ civics education achievement in which those in experimental group reached higher mean score than those in the control group. Thus, the conclusion of this study responsed to the aims of the research as follows: (1) Quantum Learning Cycles of EEL Dr. C is effective in maximizing students’ achievement; (2)